COMPARISON OF BLOOD CHOLESTEROL PROFILES BEFORE AND AFTER THE MEASUREMENTS OF MAXIMUM AEROBIC CAPACITY (VO2MAX) - Shadiqin, AR (Vidya Karya Jurnal Kependidikan, 2013)
This study aimed to compare the blood cholesterol profile, before and after the measurement of maximum aerobic capacity (VO2max) in the students of Sports and Healthy Department (JPOK) FKIP UNLAM. Variables in this study consist of lipid profiles, including total cholesterol, HDL, LDL, triglyceride and VO2max. Operationally, VO2max referred in this study is the maximum volume of oxygen that can be consumed per minute, as measured at progressive run (Bleep Test). The method used in this study is pre-experimental with one group pretest-posttest design. The study showed that there are changes in blood cholesterol profile after the measurement of VO2max, shown by significant decrease of total cholesterol variable, increased HDL, and decreased LDL. Changes in triglyceride variable showed no significant decrease despite the statistic differences. Specific HDL sub-class increasing after exercise is a constructive lipoprotein sub-class whereas LDL is destructive lipoproteins sub-class that might damage the body. Therefore, an increase in HDL and decrease in LDL found in this study appears to be advantageous and consequently might alter the risk of coronary heart disease.